An Air-Rechargeable Zn Battery Enabled by Organic–Inorganic Hybrid Cathode - Shi, Junjie; Mao, Ke; Zhang, Qixiang; Liu, Zunyu; Long, Fei; Wen, Li; Hou, Yixin; Li, Xinliang; Ma, Yanan; Yue, Yang; Li, Luying; Zhi, Chunyi; et al. (Nano-Micro Letters, 2023)
Self-charging power systems collecting energy harvesting technology and batteries are attracting extensive attention. To solve the disadvantages of the traditional integrated system, such as highly dependent on energy supply and complex structure, an air-rechargeable Zn battery based on MoS2/PANI cathode is reported. Benefited from the excellent conductivity desolvation shield of PANI, the MoS2/PANI cathode exhibits ultra-high capacity (304.98 mAh g−1 in N2 and 351.25 mAh g−1 in air). In particular, this battery has the ability to collect, convert and store energy simultaneously by an air-rechargeable process of the spontaneous redox reaction between the discharged cathode and O2 from air. The air-rechargeable Zn batteries display a high open-circuit voltage (1.15 V), an unforgettable discharge capacity (316.09 mAh g−1 and the air-rechargeable depth is 89.99%) and good air-recharging stability (291.22 mAh g−1 after 50 air recharging/galvanostatic current discharge cycle). Most importantly, both our quasi-solid zinc ion batteries and batteries modules have excellent performance and practicability. This work will provide a promising research direction for the material design and device assembly of the next-generation self-powered system. Highlights: 1 The excellent performance of MoS2/PANI cathode is due to better conductivity and desolvation shielding. 2 The self-charging zinc battery was successfully assembled that achieve deep self-discharge and long cycle life. 3 The quasi solid state battery and battery module have excellent performance and practicability.